Harnessing Ultrafast Optical Pulses for 3D Microfabrication by Selective Tweezing and Immobilization of Colloidal Particles in an Integrated System - Krishangi Krishna; Jieliyue Sun; Wenyu Liu; Robert H. Hurt; Kimani C. Toussaint Jr. (Advanced Photonics Research)
Microfabrication using nano‐ to micron‐sized building blocks holds a great potential for applications in next‐generation electronics, optoelectronics, and advanced materials. However, traditional methods like chemical vapor deposition and molecular beam epitaxy require highly controlled environments and specialized equipment, limiting scalability and precision. To address these challenges, a single‐laser platform is presented for selective tweezing and immobilization of colloids (STIC) that integrates particle manipulation, assembly, and stabilization in one system. STIC utilizes a femtosecond laser at ultra‐low power for precise, contact‐free optical manipulation of colloids without material damage. At higher power, the same laser enables two‐photon polymerization (TPP) to immobilize colloids securely in their intended positions. Using STIC, the assembly of 3D structures from dielectric beads to patterned arrangements of transition metal dichalcogenides (TMDs e.g., MoS2) is demonstrated. Also a TPP‐fabricated handle as an intermediate support is incorporated which significantly enhances the optical tweezing efficiency of TMDs. The single‐laser design eliminates the need for dual‐laser systems, simplifying optical alignment, reducing heat damage, and improving efficiency. Additionally, it is shown that STIC supports direct multiphoton imaging for in situ inspection during fabrication. This work establishes a versatile, scalable optical platform for high‐precision microstructure fabrication, offering a pathway to overcome current limitations in micro‐ and nanomanufacturing.